Implementasi Aplikasi Point of Sale pada Toko Oli Special Teknik di Kabupaten Bireuen - Islahul Lana Putri, T. Irfan Fajri, J. Prayoga (LPPM-UNIKI, 2024)
The Point of Sale (POS) application for Toko Oli Special Teknik aims to enhance data security as well as facilitate the integration of inventory management and financial monitoring. This application was developed for Toko Oli Special Teknik in Kabupaten Bireuen using the waterfall method, chosen for its suitability in developing applications with clear and stable requirements. The implementation of this application has demonstrated several advantages for users, including: enhanced data security to ensure customer data is well-protected, improved service availability with easy and quick access for store employees, both cashiers and administrators, and better integration with external systems such as financial management systems, thereby increasing operational efficiency. Based on the analysis and beta testing conducted on this POS application, it has been proven to operate effectively and meet the needs of Toko Oli Special Teknik.